Noninvasive in toto imaging of the thymus reveals heterogeneous migratory behavior of developing T cells - Bajoghli, Baubak; Inoue, Daigo; Aghaallaei, Nargessadat; Thumberger, Thomas; Wittbrodt, Joachim (The journal of immunology, 2015)
The migration of developing T cells (thymocytes) between distinct thymic microenvironments is crucial for their development. Ex vivo studies of thymus tissue explants suggest two distinct migratory behaviors of thymocytes in the thymus. In the cortex, thymocytes exhibit a stochastic migration, whereas medullary thymocytes show confined migratory behavior. Thus far, it has been difficult to follow all thymocytes in an entire thymus and relate their differentiation steps to their migratory dynamics. To understand the spatial organization of the migratory behavior and development of thymocytes in a fully functional thymus, we developed transgenic reporter lines for the chemokine receptors ccr9a and ccr9b , as well as for rag2 , and used them for noninvasive live imaging of the entire thymus in medaka ( Oryzias latipes ). We found that the expression of these two chemokine receptors in the medaka juvenile thymus defined two spatially distinct subpopulations of thymocytes. Landmark events of T cell development including proliferation, somatic recombination, and thymic selection can be mapped to subregions of the thymus. The migratory behavior of thymocytes within each of the subpopulations is equally heterogeneous, and specific migratory behaviors are not associated with particular domains in the thymus. During the period when thymocytes express rag2 their migratory behavior was more homogeneous. Therefore, the migratory behavior of thymocytes is partly correlated with their developmental stage rather than being defined by their spatial localization.
Gesehen am 31.01.2017